Patients' Experiences Before, During, and After a Colonoscopy Procedure: A Qualitative Study. (28th November 2021) - Rosvall, Annica; Axelsson, Malin; Toth, Ervin; Kumlien, Christine; Annersten Gershater, Magdalena
Abstract : Although colonoscopy is a common examination, there is limited research focusing on how patients experience this procedure. It is important that a colonoscopy is tolerated, as it may lead to lifesaving diagnostics and treatment. This study aims to explore adult patients' experience of undergoing a colonoscopy regarding the time prior to, during, and after the procedure. This was a qualitative study with individual interviews ( n = 24) and a purposeful sample that was analyzed using thematic analysis. The analysis revealed four themes. The first, " making up one's mind, " describes how the participants gathered information and reflected emotionally about the forthcoming procedure. The hope of clarification motivated them to proceed. In the theme " getting ready, " self-care was in focus while the participants struggled to follow the instructions and carry out the burdensome cleansing. The next theme, " going through, " illuminates' experiences during the colonoscopy and highlights the importance of feeling involved and respected. The last theme, " finally over, " is characterized by experiences of relief, tiredness, and a desire for clarity. The healthcare professionals' ability to meet the participants' needs is vital, given that the experiences are highly individual. These findings contribute to a variegated image of how patients experience the process of undergoing a colonoscopy.